Composite Volume Learning Media Based on Augmented Reality to Enhance Students' Visual-Spatial Intelligence - Kurniawati, Ria; Susiswo, Susiswo; Hadi, Syamsul (Sekolah Pascasarjana Universitas Negeri Malang (UM), 2024)
Augmented Reality (AR) technology, a three-dimensional visual tool that integrates virtual objects or environments into real-world displays in real time (Azuma et al., 2001), is particularly useful for grasping complex concepts such as the composite volume of solids, which often confuses students when they need to decompose solids into their individual components. While previous research has predominantly focused on the introduction of solids, spatial nets, and the volume of singular shapes, this study aims to develop composite volume learning media based on AR to enhance students’ visual-spatial intelligence in a valid, practical, and effective manner, aligning with their concrete operational stages. The development of this media follows the design-based research model proposed by Klopfer and Squire (2008) and Hadjistassou et al. (2021), encompassing stages such as brainstorming, design, development, field trials, and classroom implementations. The integration of Blender, Unity 3D, and Vuforia has been employed to create user-friendly learning media. Although the media was validated in terms of content and material, with suggestions for improving interactivity, enrichment questions, flexibility of access, and display design, its effectiveness was not statistically significant. Nevertheless, with proper implementation during appropriate learning stages and methods, the media could potentially benefit other aspects of intelligence, such as interpersonal, intrapersonal, and logical-mathematical intelligences. To fully assess the media’s effectiveness, the application of Multiple Intelligences Research (MIR) tests is recommended.DOI: 10.17977/jps.v12i42024p132